Loot box engagement: relationships with educational attainment, employment status and earnings in a cohort of 16 000 United Kingdom gamers. (22nd February 2022) - Close, James; Spicer, Stuart Gordon; Nicklin, Laura Louise; Lloyd, Joanne; Lloyd, Helen
Abstract: Background and Aims: Loot boxes are purchasable randomised rewards in video games that share structural and psychological similarities with gambling. Systematic review evidence has established reproducible associations between loot box purchasing and both problem gambling and problem video gaming. We aimed to measure the association between loot box engagement and socioeconomic correlates. Design: The study was a cross‐sectional online survey using the recruitment platform, Prolific. Setting: United Kingdom (UK). Participants: A cohort of 16 196 UK adults (18 + years) self‐reporting as video gamers. Measurements: Respondents were asked about their game‐related purchasing behaviour (including loot boxes), recent monthly spend on loot boxes and gambling engagement (gambling in any form; gambling online; playing 'social casino' games). A range of demographic variables were simultaneously captured, including age, sex, ethnicity, earnings, employment and educational attainment. Findings: Overall, 17.16% of gamers in our cohort purchased loot boxes, with a mean self‐reported monthly spend of £29.12. These loot box purchasers are more likely to gamble (45.97% gamble) than people who make other types of game‐related purchases (on aggregate, 28.13% of non‐loot box purchasers gamble), and even greater still than those who do not make any game related purchases (24.38% gamble P < 0.001). Loot box engagement (as binary yes/no or as monthly spend normalised to earnings) was significantly associated with younger age ( P < 0.001 and P < 0.001; respectively, for binary yes/no and monthly spend, adjusted for false discovery rate correction), male sex ( P < 0.001 and P = 0.025), non‐university educational attainment ( P < 0.001 and P < 0.001) and unemployment ( P = 0.003 and P = < 0.001). Lower earners spent a higher proportion of monthly earnings on loot boxes ( P < 0.001). Conclusions: The demographic associations of video game loot box engagement (younger age, male sex, non‐university educational attainment and unemployment) mirror those of other addictive and problematic behaviours, including disordered gambling, drug and alcohol misuse.